Al Maktoum bridges, UAE: condition evaluation, assessment and durability analysis. Issue 1 (3rd March 2022) - Christodoulou, Christian; Dodds, Wayne
Abstract : This paper presents a case study of the condition evaluation, structural assessment and durability analysis of the Al Maktoum bridges in the UAE to provide assurance that they will meet their 100-year service life. It is considered that this holistic analysis is the first of its kind in the UAE. The project included a detailed structural assessment utilising three-dimensional finite-element methods. The analysis indicated that the stresses in all the critical elements were well below the yield limit. The results of the structural assessment were used in combination with the durability assessment to inform the life cycle cost analysis and asset maintenance strategy. The durability analysis incorporated a probabilistic assessment method to verify the remaining service life of the structures. This method utilised a 90% confidence level using the fib Model Code for Service Life Design . The results of modelling were verified against the inspection and testing results, which included concrete strength tests, half-cell potential mapping and chloride ion sampling. Overall, this project case is the first of its kind in the UAE and provided a platform of asset management strategy implementation to establish the current condition of the structures, assess their structural integrity and verify their remaining service life.